Comparison of overpass / underpass in the light of various parameters: Karabuk-Safranbolu case study - Yumrutaş, Halil İbrahim; Sarısoy, Şeyda Çınar (Afyon Kocatepe Üniversitesi)
Concrete, stone, steel, and wooden materials are used in the construction of pedestrian over/underpasses. However, there has still been uncertainty when preferring the construction of over or underpass. In this study, an inventory of pedestrian overpasses and underpasses in Karabuk-Safranbolu region was presented in the light of various parameters. Two kinds of overpasses (constructed as steel and reinforced concrete) and an underpass were selected, and cost analyses were carried out comparatively. Additionally, face-to-face surveys were carried out with 300 people in 3 different over/underpass locations, and the results were evaluated by SPSS (statistical package for social sciences) ANOVA (analysis of variance). The advantages and disadvantages of over/underpasses in terms of cost, safety, ease of use/comfort, saving of time, user preference, aesthetic, construction period are revealed by means of the survey studies, data collected by General Directorate of Highways (KGM) and on-site observations, and then presented with tables and graphics. There has not been any standard, regulation, code, or design and safety criteria for the construction of underpasses/overpasses in our country and it is thought that this study will contribute to decision-making process of related authorities such as municipalities, general directorate of highways, etc.

Yaya geçitlerinin inşasında ahşap, betonarme, çelik veya kompozit malzemeler kullanılmaktadır. Ancak günümüzde, inşa edilecek olan yaya üst/altgeçitlerinden hangisinin tercih edilmesi gerektiği hususunda çeşitli belirsizlikler bulunmaktadır. Bu çalışmada Karabük-Safranbolu bölgesinde yer alan yaya üst ve altgeçitlerinin çeşitli parametreler ışığında bir envanteri oluşturulmuştur. Çelik ve betonarme olarak inşa edilmiş iki farklı üstgeçit ile bir altgeçit seçilerek mukayeseli bir şekilde maliyet analizleri yapılmıştır. Ayrıca 3 farklı lokasyonda her biri 100’er kişi olmak üzere toplamda 300 kişiyle yüz yüze anket çalışmaları gerçekleştirilmiş, elde edilen sonuçlar SPSS (statistical package for social sciences) ANOVA (analysis of variance) ile değerlendirilmiştir. Anket çalışmaları, Karayolları Genel Müdürlüğü’nden (KGM) elde edilen veriler ve yerinde gözlemler ile kullanıcılar tarafından ortaya konulan güvenlik, kullanım kolaylığı/konfor, zaman tasarrufu, altgeçit/üstgeçit tercihi, estetiklik gibi hususlarda avantaj ve dezavantajları tablo ve grafikler eşliğinde ortaya konulmuştur. Ülkemizde altgeçit/üstgeçitlerin imalatında yeterli düzeyde standart, tasarım ve güvenlik kriteri bulunmamakta olup çalışmanın Belediyeler, KGM gibi yetkili mercilerin karar verme süreçlerinde yararlanabileceği bir kaynak olacağı düşünülmektedir.
Muhtelif parametreler ışığında üstgeçit/altgeçit mukayesesi: Karabük-Safranbolu örneği
Keywords: Overpass; Underpass; Culvert; SPSS; ANOVA; Üstgeçit; Altgeçit; Menfez; SPSS; ANOVA